Burlesk Queen - Ad Castillo, Celso; Ian Film Production (Firm). ([s.l.] Ian Film Production, 2003)
To support her paralytic father, Chato works as a utility girl for burlesque star Virgie Nite. But when Virgie gets drunk on the night of her scheduled performance, Chato pitches in for Virgie if only to appease the furious crowd.. and Chato becomes an instant sensation. Enthused by the initial acceptance of the audience, she defies her father's admonitions and presents herself to the manager. And, thus, becoming the new burlesque queen. More events follow turning her once simple and peaceful life 180 degrees.
VCD
Directed by Celso Ad Castillo.
Vilma Santos
Keywords: Feature films